TEACHER'S EXPERIENCE IN TEACHING SPEAKING BY USING STAD - Ariesa, Adha; Sudarsono, Sudarsono; Suhartono, Luwandi (Journal of English Education Program, 2021)
This research was aimed to describe the teacher's experience in teaching speaking using STAD. The subject of this research was an English teacher of SMAN 10 Pontianak who was experienced in teaching English by using STAD. This research was a case study to describe the teacher's experience while using STAD in teaching speaking. The data were collected from interviews, audio-visual materials, and document reviews. The speaking score of 36 students from the Year-10 students of SMAN 10 Pontianak in Academic Year 2019/2020 was used in this research. The results showed that the STAD technique affected the students' speaking learning achievement as much as 9 out of 36 students experienced an increase in their score by 4%. Some internal factors contributed to those students' achievement, namely, students' contributions, motivating students, and improving student skills. Moreover, the findings revealed that some students did not achieve the goal of learning by using STAD. This is caused by several factors, namely managing time, managing class, and lack of speaking skills become the difficulties of this research.Keywords: Case Study, Experience, STAD, Speaking Skill.